Guillain-Barré Syndrome Secondary to Herpes Zoster: A Rare Case Report of Death and Literature Review - Jingyu Wang; Xinyi Hou; Jin Zhang; Bo Ren; Bin Lu (Case Reports in Dermatology)
Introduction: Herpes zoster (HZ) is a common infectious skin disease, and postherpetic neuralgia is the most feared and common complication. Guillain-Barré syndrome (GBS) is a rare complication of HZ. Case Presentation: An exceptional case presenting GBS following HZ with a subsequent lethal issue is presented. A review of literature data revealed that middle-aged men with HZ were more likely to develop GBS. In the early stages of the disease, absent tendon reflexes and numbness of the limbs were common in patients. Conclusion: GBS should be kept in mind as rare HZ complication, particularly in middle-aged male patients.